THE POTENTIAL EFFECT OF DECREASED LUNG FUNCTION ON SLEEP QUALITY OF FARMERS IN KELURAHAN ANTIROGO KECAMATAN SUMBERSARI KABUPATEN JEMBER: POTENSI PENGARUH PENURUNAN FUNGSI PARU TERHADAP KUALITAS TIDUR PETANI DI KELURAHAN ANTIROGO KECAMATAN SUMBERSARI KABUPATEN JEMBER - Prastiani, Ananda Eka; Nuraini, Niken Sari; Dwi Hapsari, Purti Inayah (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2022)
Introduction: Indonesia is an agrarian country with the majority of its population working in the agricultural sector. The Indonesian agricultural sector ranks first in the number of workplace accidents, including the incidence of lung disease. The factors that most influence respiratory problems in farmers are the result of exposure to pesticides and unhealthy smoking behavior. Lung disease experienced by farmers often affects sleep quality. Poor sleep quality is caused by shortness of breath, coughing, and excessive production of secretions. Inadequate sleep causes physical disturbances. This study aims to analyze the potential effect of decreased lung function on the sleep quality of farmers. Methods: This is a quantitative research that uses interviews with respondents using two questionnaires. The research sample used purposive sampling with 38 respondents in Kelurahan Antirogo, Kecamatan Sumbersari, Kabupaten Jember. The instruments used are the Lung Functioning Questionnaire and the Pittsburgh Sleep Quality Index (PSQI) and the correlation between variables was evaluated using Paired T-Test. Result: The results show that there is a significant decrease in the value of Sig. (2-tailed) 0.000 (p < 0.05). The explanation was added by linking the discussion to decreased lung function on the Lung Functioning Questionnaire indicators, such as cough intensity, additional breath sounds, shortness of breath, and duration of smoking. In addition, a discussion was also given regarding the decline in lung function by type of gender, age, education, and occupation. Conclusion: An indication of decreased lung function is a factor that can affect sleep quality.